1991
DOI: 10.1111/j.1365-2125.1991.tb05512.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical differences in adverse drug reaction reporting rates in the Northern Region.

Abstract: The reporting rates of adverse drug reactions in the Northern Region have been examined with respect to source (hospital or general practice) and district of origin for the 3 years 1986‐88. Mean annual reporting rates, corrected for population, or clinical activity, varied approximately 4‐fold in general practice (0.066 to 0.257 reports per 1000 resident population) and more than 12‐fold in hospitals (0.14 to 1.77 reports per 1000 deaths and discharges). There was no correlation between hospital and general pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 3 publications
11
55
5
Order By: Relevance
“…Also this finding was comparable to those from other similar studies done by Qing L et al, and Belton KJ et al, but was not comparable to the findings by Bateman et al 20,[23][24][25] A large number of interns (42%) did not know the actual procedure of reporting ADRs. When enquired further, they revealed that they found difficulty in filling the form, as to where the ADRs be reported and also to whom they should be reported.…”
Section: Discussionsupporting
confidence: 79%
“…Also this finding was comparable to those from other similar studies done by Qing L et al, and Belton KJ et al, but was not comparable to the findings by Bateman et al 20,[23][24][25] A large number of interns (42%) did not know the actual procedure of reporting ADRs. When enquired further, they revealed that they found difficulty in filling the form, as to where the ADRs be reported and also to whom they should be reported.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the response rate of participants was 73.25 % which is similar to that shown by Desai et al who reported a response rate of 70.7% in resident doctors [15] ADRs contribute significantly to morbidity and mortality in clinical practice with its associated economic consequences [16]. Studies from developed economies such as UK and USA have reported a higher rate of ADR reporting and higher awareness among healthcare professionals about pharmacovigilance [17,18 ]. while current contribution of India to global safety database is 3% [19] In our study, the perception is high which is similar to study from India which has reported encouraging findings regarding attitudes and perceptions of medical practitioners about pharmacovigilance [20] Spontaneous ADR reporting is a vital method for detecting new safety issues related to drugs.But reporting the same exclusively in resident doctors was observed in very few studies.…”
Section: Discussionsupporting
confidence: 73%
“…12 Another study conducted by Bateman et al, revealed that the amount of time taken to report an ADR is the major determinant for low ADR reporting while other factors are lack of appreciation of ADR reporting, complexity of the ADR reporting process and the belief that it was not their responsibility to report ADR. 13 Uncertainty regarding the causal relationship between the event and the suspected drug is also a barrier for ADR reporting by Vallono et al 14 Around 95% of resident doctors and 90% of nursing staff think that ADR reporting is necessary, which again coincide with the results obtained by Li Qing et al 11 But not with those which were obtained by Bateman et al 13 Moreover, large proportion of health care workers expect feedback from ADR monitoring center. Some of the resident doctors and nursing staff think that ADR reporting may damage their professional image, while others agree that ADR reporting is a time-consuming activity without any outcome.…”
Section: Discussioncontrasting
confidence: 44%